2016
DOI: 10.3390/ijms17111888
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin A2 Modulates IL-4-Induced CCL26 Production in Human Alveolar Epithelial Cells

Abstract: Allergic asthma is an inflammatory lung disease that is partly sustained by the chemokine eotaxin-3 (CCL26), which extends eosinophil migration into tissues long after allergen exposure. Modulation of CCL26 could represent a means to mitigate airway inflammation. Here we evaluated procyanidin A2 as a means of modulating CCL26 production and investigated interactions with the known inflammation modulator, Interferon γ (IFNγ). We used the human lung epithelial cell line A549 and optimized the conditions for indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…On the other hand, LPS-stimulated macrophage is a classic model of inflammatory responses in vitro [ 33 ]. Previous studies revealed that PCA2 has the effects of protecting cells from oxidation, inflammation, such as human monocyte macrophages (THP-1) [ 26 ] and L0-2 cells [ 35 ], A549 cells [ 24 ], and BV2 cells [ 36 ], respectively. PCA2 exhibited anti-inflammatory activity via suppressing CCL-26 production in IL-4-stimulated A549 cells [ 24 ] and anti-oxidative activity via modulating the Nrf2 pathway in tert -butyl hydroperoxide-stimulated L0-2 cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, LPS-stimulated macrophage is a classic model of inflammatory responses in vitro [ 33 ]. Previous studies revealed that PCA2 has the effects of protecting cells from oxidation, inflammation, such as human monocyte macrophages (THP-1) [ 26 ] and L0-2 cells [ 35 ], A549 cells [ 24 ], and BV2 cells [ 36 ], respectively. PCA2 exhibited anti-inflammatory activity via suppressing CCL-26 production in IL-4-stimulated A549 cells [ 24 ] and anti-oxidative activity via modulating the Nrf2 pathway in tert -butyl hydroperoxide-stimulated L0-2 cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Procyanidin, polyphenolic secondary metabolites, is a compound formed by the polymerization of flavan-3-ol as a structural unit through C-C bond, and its mechanism is currently unclear [24]. Procyanidin A2 (PCA2) is an A-type proanthocyanidin dimer formed by the polymerization of epicatechin ( Fig 1A) and preponderantly locate in the nucleus, shell, seed, flower, and leaves of many plants [24]. Specifically, the content of PCA2 is occupies a large percentage in grape seeds [25].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds reported to have immune enhancing properties include food ingredients or are found in natural immune-boosting whole foods. In addition, many studies are working on identifying plant compounds that target specific cellular events and complement the body's own immune actions upon exposure to known allergens such as air pollution (Coleman, Kruger, Sawyer, & Hurst, 2016;Sawyer, Stevenson, McGhie, & Hurst, 2017). In any event it is likely that the results from such research will support the development of functional foods with beneficial biological activities to help the immune system recover from the impact of air pollution (Nyanhanda et al, 2014).…”
Section: Potential Of Functional Foods To Help the Immune Systemmentioning
confidence: 99%
“…These dietary‐related improvements in lung function benefits are also seen in people living in polluted environments (Burbank et al., 2018; Pounis et al., 2018; Stevens et al., 2019). Fruits and vegetables contain numerous bioactive compounds, including anthocyanins and procyanidins, which have been shown to attenuate lung inflammation in cell and animal models of allergy and asthma (Coleman et al., 2016; Coleman & Shaw, 2017; Park et al., 2007; Sawyer et al., 2017; Shaw et al., 2016, 2017). Human population studies have identified that dietary intake of foods high in polyphenols and tetraterpenes (Pounis et al., 2018) such as apples, pears (Garcia‐Larsen et al., 2018), carrots, tomatoes (Rosenlund et al., 2011), and citrus is inversely correlated with the frequency and severity of reported asthma symptoms, especially wheezing and coughing (Garcia et al., 2005; Garcia‐Larsen et al., 2018; McKeever & Britton, 2004; Rosenlund et al., 2011).…”
Section: Introductionmentioning
confidence: 99%